2018
DOI: 10.5194/esd-9-785-2018
|View full text |Cite
|
Sign up to set email alerts
|

Tagging moisture sources with Lagrangian and inertial tracers: application to intense atmospheric river events

Abstract: Abstract. Two Lagrangian tracer tools are evaluated for studies on atmospheric moisture sources and pathways. In these methods, a moisture volume is assigned to each particle, which is then advected by the wind flow. Usual Lagrangian methods consider this volume to remain constant and the particle to follow flow path lines exactly. In a different approach, the initial moisture volume can be considered to depend on time as it is advected by the flow due to thermodynamic processes. In this case, the tracer volum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Atmospheric rivers have also been described using Lagrangian trajectories in an Earth‐relative framework, for example in Pérez‐Muñuzuri et al . (2018) and Sodemann et al . (2020).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Atmospheric rivers have also been described using Lagrangian trajectories in an Earth‐relative framework, for example in Pérez‐Muñuzuri et al . (2018) and Sodemann et al . (2020).…”
Section: Introductionmentioning
confidence: 95%
“…Since they are defined using a vertically integrated measure, atmospheric rivers are 2-dimensional features. Atmospheric rivers have also been described using Lagrangian trajectories in an Earth-relative framework, for example in Pérez-Muñuzuri et al (2018) and Sodemann et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…While HPEs are a regional phenomena, moisture feeding them not only comes from nearby sea evaporation but can originate in remote regions and be transported by different atmospheric mechanisms. In this sense, it has been shown that long-distance moisture transport through atmospheric rivers (ARs) is a crucial contributor to total precipitation amounts recorded in Europe and the United States (e.g., Lavers and Villarini, 2015;Hu and Dominguez, 2019;Pérez-Muñuzuri et al, 2018) and also to extreme rainfall episodes (e.g., Stohl et al, 2008;Eiras-Barca et al, 2017). As for the WMR, recent studies (e.g., Winschall et al, 2012;Pinto et al, 2013;Krichak et al, 2015;Insua-Costa et al, 2019) suggest that remote sources of moisture such as the North Atlantic or tropical or subtropical areas could contribute significantly to the frequent torrential rains there.…”
Section: Introductionmentioning
confidence: 99%